Fine mapping of QGPC.caas-7AL for grain protein content in bread wheat - Dehui Zhao; Jianqi Zeng; Hui Jin; Dan Liu; Li Yang; Xianchun Xia; Yubing Tian; Yan Zhang; Shuanghe Cao; Wei Zhu; Chunping Wang; He Zhonghu; et al. (Springer, 2024)
Wheat grain protein content (GPC) is important for end-use quality. Identification of genetic loci for GPC is helpful to create new varieties with good processing quality and nutrients. Zhongmai 578 (ZM578) and Jimai 22 (JM22) are two elite wheat varieties with different contents of GPC. In the present study, 262 recombinant inbred lines (RILs) derived from a cross between ZM578 and JM22 were used to map the GPC with high-density wheat Illumina iSelect 50 K single-nucleotide polymorphism (SNP) array. Seven quantitative trait loci (QTLs) were identified for GPC on chromosomes 3AS, 3AL, 3BS, 4AL, 5BS, 5DL and 7AL by inclusive composite interval mapping, designated as QGPC.caas-3AS, QGPC.caas-3AL, QGPC.caas-3BS, QGPC.caas-4AL, QGPC.caas-5BS, QGPC.caas-5DL and QGPC.caas-7AL, respectively. Among these, alleles for increasing GPC at QGPC.caas-3AS, QGPC.caas-3BS, QGPC.caas-4AL and QGPC.caas-7AL loci were contributed by ZM578, whereas those at the other three loci were from JM22. The stable QTL QGPC.caas-7AL was fine mapped to a 1.82-Mb physical interval using secondary populations from six heterozygous recombinant plants obtained by selfing a residual RIL. Four genes were predicted as candidates of QGPC.caas-7AL based on sequence polymorphism and expression patterns. The near-isogenic lines (NILs) with the favorable allele at the QGPC.caas-7AL locus increased Farinograph stability time, Extensograph extension area, extensibility and maximum resistance by 19.6%, 6.3%, 6.0% and 20.3%, respectively. Kompetitive allele-specific PCR (KASP) marker for QGPC.caas-7AL was developed and validated in a diverse panel of 166 Chinese wheat cultivars. These results provide further insight into the genetic basis of GPC, and the fine-mapped QGPC.caas-7AL will be an attractive target for map-based cloning and marker-assisted selection in wheat breeding programs.